Mensajes del inframundo Las kleksografías de Justinus Kerner - Montiel, LUIS (Escritura e Imagen, 2005)
At the end of his life the German doctor and poet Justinus Kerner (1786-1862), one of the main exponents of the romantic style in medicine, invented a very personal pictorial-literary genre: klecksography. Based on images formed by ink-blots, he composed poems that identified them as emissaries of the underworld, breaking through into our world thanks to the invisible force of animal magnetism. This article presents translations of some of the klecksographies that were the object of a posthumous publication.